2013
DOI: 10.1177/1756285613488434
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender issues in multiple sclerosis

Abstract: Multiple sclerosis (MS) is universally found to be more prevalent in women than men. This has led to extensive studies of differences in the immune system or nervous system between women and men, which might be caused by the effects of gonadal hormones, genetic differences, and different environmental exposures and modern lifestyle in men and women. We review the effects of sex and gender from a genetic, immunological and clinical point of view. We discuss the effects of sex on the clinical expression of MS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
271
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(297 citation statements)
references
References 106 publications
21
271
1
4
Order By: Relevance
“…In a recent study, the annual incidence of MS in Iran was reported to be 5.9 per 100,000 people and the point prevalence in the Fars province of Iran was estimated to be 72 per 100,000 (Etemadifar et al., 2014; Izadi, Nikseresht, Poursadeghfard, Borhanihaghighi, & Heydari, 2015). The prevalence of the disease may be affected by gender, being more prevalent in women than in men (Harbo, Gold, & Tintore, 2013). Consequently, women are at higher risk of morbidity and should be considered a vulnerable population in whom the development of effective interventions is a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the annual incidence of MS in Iran was reported to be 5.9 per 100,000 people and the point prevalence in the Fars province of Iran was estimated to be 72 per 100,000 (Etemadifar et al., 2014; Izadi, Nikseresht, Poursadeghfard, Borhanihaghighi, & Heydari, 2015). The prevalence of the disease may be affected by gender, being more prevalent in women than in men (Harbo, Gold, & Tintore, 2013). Consequently, women are at higher risk of morbidity and should be considered a vulnerable population in whom the development of effective interventions is a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic risk MS is a complex disease involving interactions between environmental and genetic factors, with epigenetic mechanisms likely involved [Harbo et al 2013;Küçükali et al 2015]. Patients are concerned about risk to their children.…”
Section: Female Versus Male Patientsmentioning
confidence: 99%
“…8 However, these studies do not control for patients who were ultimately diagnosed with MS, which has a strong female predominance. 24 Of four class III retrospective cohort surveys examined in a recent evidence-based guideline, 25 two reported that more women than men are diagnosed with inflammatory myelopathies in association with MS, 4,26 but none showed a sex association in idiopathic TM. 4,16,26,27 In this total study population, 54% were female, but within the local Emirati population, 82% of participants were female.…”
Section: Discussionmentioning
confidence: 99%